The Efficacy and Safety of Topical Saline Irrigation with Tranexamic Acid on Perioperative Blood Loss in Patients Treated with Percutaneous Endoscopic Interlaminar Diskectomy: A Retrospective Study - Zhang, Yu; Zhao, Wenjie; Hu, Man; Liu, Xin; Peng, Qing; Meng, Bo; Yang, Sheng; Feng, Xinmin; Zhang, Liang (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Background Tranexamic acid (TXA) is safe and effective in preventing bleeding during spinal surgery. However, there is currently no relevant research on the efficacy and safety of adding TXA to the saline irrigation fluid in percutaneous endoscopic interlaminar diskectomy (PEID). This study aimed to evaluate the efficacy and safety of topical saline irrigation with TXA for PEID in the treatment of lumbar disk herniation.Methods In this single-center, retrospective cohort study, patients who underwent PEID for L5–S1 lumbar disk herniation were included and allocated to two groups according to whether they had been administered TXA. PEID was performed with saline irrigation fluid containing 0.33 g of TXA per 1 L of saline in the TXA group (n = 38). In the control group (n = 51), the saline irrigation fluid was injected with the same volume of normal saline. All PEIDs were performed by the same spine surgery team. The hidden blood loss (HBL), intraoperative blood loss (IBL), total blood loss (TBL), amount of fluid used, operation time, visual clarity, hospital stay, blood transfusion rate, coagulation index, and complication rate were compared between the two groups.Results The TBL, HBL, and IBL in the TXA group were significantly lower than those of the control group. The postoperative hemoglobin in the TXA group was significantly higher than that of the control group. Visual clarity was significantly better and the operation time was significantly shorter in the TXA group. However, there was no significant difference in postoperative hematocrit, blood coagulation function, amount of fluid used, blood transfusion rate, and perioperative complications between the two groups.Conclusion In PEID, the addition of TXA to topical saline irrigating fluid can significantly reduce the HBL, IBL, and TBL. The addition of TXA to topical saline irrigating fluid can improve visual clarity in the surgery and reduce operation time, but it does not change the coagulation function or the complication rate.
Keywords: hidden blood loss; percutaneous endoscopic interlaminar diskectomy; tranexamic acid; topical; visual clarity